Thiamin dynamics during the adult life cycle of Atlantic salmon (Salmo salar) - Dahlgren, Elin; Söderberg, Linda (2024)
Thiamin is an essential water-soluble B vitamin known for its wide range of metabolicfunctions and antioxidant properties. Over the past decades, reproductive failuresinduced by thiamin deficiency have been observed in several salmonid species world-wide, but it is unclear why this micronutrient deficiency arises. Few studies havecompared thiamin concentrations in systems of salmonid populations with or withoutdocumented thiamin deficiency. Moreover, it is not well known whether and how thi-amin concentration changes during the marine feeding phase and the spawningmigration. Therefore, samples of Atlantic salmon (Salmo salar) were collected whenactively feeding in the open Baltic Sea, after the sea migration to natal rivers, afterriver migration, and during the spawning period. To compare populations of Balticsalmon with systems without documented thiamin deficiency, a population of land-locked salmon located in Lake Vänern (Sweden) was sampled as well as salmon fromNorwegian rivers draining into the North Atlantic Ocean. Results showed the highestmean thiamin concentrations in Lake Vänern salmon, followed by North Atlantic, andthe lowest in Baltic populations. Therefore, salmon in the Baltic Sea seem to be con-sistently more constrained by thiamin than those in other systems. Condition factorand body length had little to no effect on thiamin concentrations in all systems, sug-gesting that there is no relation between the body condition of salmon and thiamindeficiency. In our large spatiotemporal comparison of salmon populations, thiaminconcentrations declined toward spawning in all studied systems, suggesting that thereduction in thiamin concentration arises as a natural consequence of starvationrather than to be related to thiamin deficiency in the system. These results suggestthat factors affecting accumulation during the marine feeding phase are key forunderstanding the thiamin deficiency in salmonids.